CircCOG8 Downregulation Contributes to the Compression-Induced Intervertebral Disk Degeneration by Targeting miR-182-5p and FOXO3 - Xiang, Qian; Kang, Liang; Zhao, Kangcheng; Wang, Juntan; Hua, Wenbin; Song, Yu; Feng, Xiaobo; Li, Gaocai; Lu, Saideng; Wang, Kun; Yang, Cao; Zhang, Yukun (Frontiers in Cell and Developmental Biology, 2020)
Circular RNAs (circRNAs) have been increasingly demonstrated to play critical roles in the pathogenesis of various human diseases. Intervertebral disc degeneration (IDD) is recognized as the major contributor to lower back pain and mechanical stress is a predominant trigger for IDD. However, little is known about the part circRNAs play in the involvement of mechanical stress during IDD development. In the present study, we identified a novel circRNA and examined the role of this circRNA in compression loading induced IDD process. We detected the expression pattern of circCOG8 and observed its function in disc NP cells under mechanical stress. We conducted bioinformatics analysis, RNA immunoprecipitation experiment and reporter gene assay to unveil the mechanism of circCOG8 downregulation mediated IVD degeneration. Results showed that circCOG8 expression was obviously down-regulated by mechanical stress in disc NP cells. CircCOG8 attenuated NP cells apoptosis, intracellular ROS accumulation and ECM degradation in vitro and ex vivo. CircCOG8 directly interacted with miR-182-5p and thus modulated FOXO3 expression to affect compression induced IDD progression. Altogether, the present study revealed that circCOG8/miR-182-5p/FOXO3 pathway was an important underlying mechanism in the involvement of compression during IDD progression. Intervention of circCOG8 is a new therapeutic strategy for IDD treatment.2